2021
DOI: 10.3390/foods10102451
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activities and Mode of Action of Cymbopogon citratus, Thymus vulgraris, and Origanum heracleoticum Essential Oil Vapors against Botrytis cinerea and Their Potential Application to Control Postharvest Strawberry Gray Mold

Abstract: Gray mold caused by Botrytis cinerea is one of the most destructive postharvest decay of strawberry fruit. The present study aims to identify essential oils with antifungal activity against B. cinerea and the underlying mechanisms and their potential application in controlling postharvest decay. In the screening test, essential oils from Cymbopogon citratus (Cc), Thymus vulgraris (Tv), and Origanum heracleoticum (Oh) exhibited maximum inhibition of B. cinerea mycelial growth. The three essential oils altered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The mechanism of action of the C. citratus EO was investigated in studies [57,59] . In [59] the mechanism of action of the EO of C. citratus against B. cinerea was analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of action of the C. citratus EO was investigated in studies [57,59] . In [59] the mechanism of action of the EO of C. citratus against B. cinerea was analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Few reports on chemical composition and biological activities of the EO of O. heracleoticum are available in the literature [ 17 , 27 , 28 , 29 , 30 ]. Napoli and coworkers reported data on variation in the aromatic profile of essential oils from a 3-year cultivation trial of Origanum vulgare subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported its antimicrobial activity against the growth of Escherichia coli and Pseudomonas aeruginosa clinical strains and against postharvest phytopathogens [ 17 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Rosemary (Rosmarinus officinalis) is a widely distributed aromatic shrub with good market prospects due to its rich active ingredients that are widely used in the field of medicine, food preservation, cosmetic and other industries. [18][19][20][21] It has been demonstrated that rosemary EO has good antibacterial, antioxidant, anti-inflammatory and antitumor effects, [22,23] and is effective in alleviating depression and reducing the risk of Alzheimer's disease. [24] The richness of its functions and uses also attests to its scientific value.…”
Section: Introductionmentioning
confidence: 99%